Effect of Vacuum Heat Treatment on Microstructures and Mechanical Properties of 7A52 Aluminum Alloy-Al2O3 Ceramic Brazed Joints - Zhang, Deku; Qian, Xusheng; Li, Xiaopeng; Wang, Kehong (Frontiers in Materials, 2021)
This study investigated the interface morphology, microstructure composition and connection strength of 7A52 aluminum alloy-Al2O3 ceramic brazed joints under heat treatment conditions. Alumina ceramics were first treated with electroless nickel plating, followed by vacuum heat treatment at different temperatures. Then an Al-Si-Mg intermediate layer was placed between the treated alumina ceramic and 7A52 aluminum alloy for brazing under the conditions of welding temperature 590℃, holding time 1h, pressure 2MPa. Results showed that when heat treatment was performed at 350°C and below, the nickel-plated metal had an amorphous structure, and when performed at 400°C, the nickel-plated layer had a crystalline structure and the brittle phase Ni3P was precipitated. When the heat treatment temperature was 350℃, the joint shear strength reached the maximum, which was 68.7 MPa.